Macrophyte islands as an experimental model: new perspectives and a step-by-step protocol to access assumptions of Island Biogeography theory and habitat fragmentation - da Silva Pires, Tiago Henrique; Santorelli Junior, Sergio; de Mendonça Cardoso, Gabriel Henrique; Cezar Florentino, Alexandro; Beck Farago, Thatyla Luana; Tovar Verba, Julia (Acta Biológica Paranaense, 2023)
To evaluate whether artificially built macrophyte islands could be used as a short-term and cost-effective experimental model for the study of island biogeography and habitat fragmentation, 20 islands of two different sizes were built and fishes were sampled. Habitat complexity and source-island distance were standardized. A macrophyte bank 200 times larger than the islands was used as a source of individuals. The results show that, in four days, several fish species colonized both small and large islands. After four days, larger islands bore significantly more species than smaller ones. We raise the caveats and new perspectives for studies using this methodology, which can be largely applicable due to its cost-effectiveness in terms of materials, short time required, and flexibility.